THE UTILIZATION OF DATA ANALYTICS TO DETERMINE THE DEVELOPMENT STRATEGY FOR THE TEACHING FACTORY OF SMK GRAFIKA KOTA TANGERANG - Bambang Eko Supriyanto (RADJA PUBLIKA, 2026)
This research aims to formulate a development strategy for the Teaching Factory (TeFa) at SMK Grafika Kota Tangerang, utilizing data analytics and referencing vocational education regulations. The TeFa is crucial for preparing graduates with industry-standard skills, yet its implementation faces constraints in planning, management, and data availability. The study used a descriptive quantitative approach, employing simple statistical analysis of questionnaire data collected from respondents regarding TeFa implementation. The analysis assessed the level of data utilization in the school's planning, operations, evaluation, and decision-making. Results indicate that the use of data analytics is still moderate, specifically in program evaluation, competency mapping, and determining industry-based training needs. These findings necessitate systematically increasing data utilization, particularly for industry-based curriculum development, business collaboration, and production scheduling. The research recommends data-driven strategies, including enhancing data literacy among teachers, integrating school information systems, optimizing program evaluation, and strengthening industrial partnerships. The implications provide a foundation for school policymakers to design TeFa development that is accurate, measurable, and sustainable, thereby increasing graduate competitiveness in the job market.